The osteoporosis after ovariectomy and the differences of rat’s thyroid parafollicular cells at the time of the treatments - Namal, Emine; Taşyürekli, Mustafa (Cerrahpaşa Medical Journal, 2014)
Objectives: We performed this study on rats which applied ovariectomy for explanning the numeric, morphologic and biochemical differences on parafollicular cells and effect of estrogen, estrogen+progesterone and calcitonin on osteoporosis. Methods: We observed numerical decreasing and regression which caused by functional failure on parafollicular cell’s GER cysternas, mitochondria and Golgi and lots of excretion granules because of the cell’s excretion disorders after osteoporosis. Results: The morphological differences before and after therapy, estrogen, estrogen+progesterone and calcitonin treatments was parallel with biochemical tests. The differences of control group’s parafollicular cells were most simillar to calsitonin treatment cells after ovariectomy. Conclusion: As a result we came to conclusion that estrogen must be used carefully because of the estrogen’s proliferative effects, estrogen+progesterone can be used together because they don’t decrease the estrogen effects and calcitonin treatment is more appropirate.